Coupled effects of matric suction and temperature on the compression behaviour of loess. Issue 6 (9th August 2019) - Cheng, Qing; Tang, Chao-Sheng
Abstract : The compression behaviour of soils is related to many geotechnical engineering problems – for example, ground subsidence, foundation deformation and embankment failure. So far, research works on the coupled effects of matric suction and temperature on the compression behaviour of soils are very limited. The aim of this study was to investigate the compression behaviour of intact and compacted loess at various matric suctions and temperatures. It was found that for both intact and compacted loess, at various suctions, the preconsolidation pressure decreases with increasing temperature (thermal softening) because the double-layer repulsion force R increases with increasing temperature. The thermal softening of the preconsolidation pressure at zero suction is more significant than that at a suction of 100 kPa. This is likely because more water exists in the soil specimen at a lower suction. Heating-induced decrease in the viscosity of water affects particle movements and the yielding of the soil skeleton. Moreover, it was found that the suction effects on the thermal softening of the preconsolidation pressure of intact loess are more significant than those of the compacted specimen.